Perspectives on Social Media from Adolescents and Young Adults with Cancer. (July 2021) - Daniels, Sarah R.; Yang, Chia-Chen; Toohey, Samantha J.; Willard, Victoria W.
Background: Adolescents and young adults (AYAs) with cancer use social media in unique ways throughout treatment. The purpose of this article is to describe the social media experiences of AYAs with cancer as a means of exploring the potential impact of social media on AYA psychosocial development after diagnosis and throughout cancer treatment.Methods: Seven AYAs treated for cancer, aged 15–20 years, completed a semi-structured interview regarding their social media preferences and habits. Each interview was transcribed verbatim and de-identified. Data were coded and themes were identified via latent thematic analysis.Results: Four themes emerged regarding social media experiences for AYAs with cancer: (1) changes in audience and feedback after diagnosis; (2) attitudes about body image and peer support; (3) control over personal, familial, and societal messages about illness; and (4) maintaining normalcy despite hospital stressors.Discussion: Social media appear especially useful for promoting social and identity development as AYAs undergo cancer treatment. Specifically, social media provide spaces to negotiate body image and sense of self, to manage peer relationships, to reclaim control and independence, and to maintain normalcy. Understanding these experiences will prepare healthcare providers and caregivers to assess ongoing psychosocial development and adjustment throughout cancer treatment.